Reestructuración técnico administrativa en la empresa Industrias Alimenticias R&J S.A.S., en la ciudad de Bogotá D.C. (2019)
In the first part of the process it has been made a diagnostic, which consist in the recollection of information through the PESTAL, used as a tool for the identification of opportunities, threats, debility and strengths, whose objective was the construction of a DOFA matrix in which they would necessary strategies to decrease the risk to which it is exposed and to take advantage of the opportunities in the market. Finally it’s found in the financial study, which is clearly intended of the profitability of organization as well as its sustainability and the possible viabilities that can present in the Industrias Alimenticias R&J S.A.S., for previous compliance were analyzed factors like inversions, financial states where is found states of results, cash flow, as well as the application of financial indicators such as the internal rate of opportunities, net present values internal rate of return and finally cost benefit ratio.